2021
DOI: 10.3390/biomedicines9091220
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Activation by SARS-CoV-2 Spike S1 Protein: A Crosstalk between Endothelium and Innate Immune Cells

Abstract: Background. Emerging evidences suggest that in severe COVID-19, multi-organ failure is associated with a hyperinflammatory state (the so-called “cytokine storm”) in combination with the development of a prothrombotic state. The central role of endothelial dysfunction in the pathogenesis of the disease is to date accepted, but the precise mechanisms underlying the associated coagulopathy remain unclear. Whether the alterations in vascular homeostasis directly depend upon the SARS-CoV-2 infection of endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…To date, however, the pathogenic mechanisms underlying the hyperinflammatory response that contributes to alveolar epithelial injury remain incompletely understood. Recently, we and others demonstrated that the in vitro treatment of human macrophages with S1 of SARS-CoV-2 causes a massive release of cytokine and chemokines in the extracellular medium [17][18][19][20]; this, in turn, results in a significant strengthening of endothelial responses to the viral protein [17], sustaining the contribution of both direct and immune-mediated mechanisms in endothelial cell activation in COVID-19. In this context, the aim of the present study was to define the cellular and molecular pathways underlying the response of alveolar epithelial cells to either the spike S1 protein or to a mixture of inflammatory mediators secreted by S1-activated macrophages, so as to help clarify the pathophysiology of lung disease upon SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 90%
“…To date, however, the pathogenic mechanisms underlying the hyperinflammatory response that contributes to alveolar epithelial injury remain incompletely understood. Recently, we and others demonstrated that the in vitro treatment of human macrophages with S1 of SARS-CoV-2 causes a massive release of cytokine and chemokines in the extracellular medium [17][18][19][20]; this, in turn, results in a significant strengthening of endothelial responses to the viral protein [17], sustaining the contribution of both direct and immune-mediated mechanisms in endothelial cell activation in COVID-19. In this context, the aim of the present study was to define the cellular and molecular pathways underlying the response of alveolar epithelial cells to either the spike S1 protein or to a mixture of inflammatory mediators secreted by S1-activated macrophages, so as to help clarify the pathophysiology of lung disease upon SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, a combination of endothelial damage and inflammation leads to a hypercoagulable state that leads to the generation of microthrombi. [ 15 ] The vast and unexplored spectrum of inflammation, endothelial injury, and pulmonary microcirculatory thrombosis contributes markedly to COVID-19-related ARDS. [ 16 ] Various conditions predispose COVID-19 patients to bleeding risk disseminated intravascular coagulation, thrombocytopenia, COVID-related hemophagocytosis, complications, and overuse of anticoagulants.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA expression has been analyzed through RT-qPCR, as previously described [11], upon incubation of HLMVEC with 1 and 100 nM dDAVP for 1 or 16 h. 1 µg of cDNA was obtained through the reverse transcription of total RNA with the RevertAid First Strand cDNA Synthesis Kit (Thermo Fisher Scientific, Milano, Italy). qPCR was then performed on a StepOnePlus Real-Time PCR System (Thermo Fisher Scientific) by employing specific forward/reverse primer pairs (Table 1) and SYBR™ Green or TaqMan Gene Expression Master Mix (Thermo Fisher Scientific).…”
Section: Rt-qpcr Analysismentioning
confidence: 99%
“…The expression level of genes coding for vasopressin receptors (AVPR1A and AVPR2) was determined using the formula 2∆Ct (where ∆Ct = Ct RPL15 − Ct gene of interest ) [12], after normalization for the housekeeping gene (Ribosomal like protein 15, RPL15, Gene ID: 6138). The amount of the different genes upon treatment with dDAVP was, instead, calculated with the ∆∆Ct method [11] and expressed, relatively to RPL15, as fold change of control untreated cells (=1).…”
Section: Rt-qpcr Analysismentioning
confidence: 99%